The Colombian press and the San José galleon: A political and legal interest but not numismatic (2018)
This article presents the low interest of the Colombian press in the light of numismatic heritage found in 2015 in the wreck of the San José galleon, warship sunk in Barú (near Cartagena de Indias) in 1708. The opinions of the Kingdom of Spain about its supposed legal rights as the owner of the coins the ship was transporting has given rise to an exacerbated chauvinism and agitated the flag of anti-Spanish in several Colombian newspapers, a situation that fortunately seems already overcome. © 2018 Ediciones Hecate. All rights reserved.